Collaboration, confrontation, and controversy: the politics of monument restoration in Georgia and the case of Bagrati Cathedral. Issue 4 (20th November 2018) - Long, Michael
Abstract : This paper examines the history of the restoration, or more accurately, reconstruction of Bagrati Cathedral in western Georgia. Constructed in 1003, Bagrati Cathedral is an important cultural monument in the political and architectural history of Georgia. Destroyed by an explosion in 1691, the cathedral was inscribed on UNESCO's World Heritage List in 1994 in its ruined state. However, the Georgian government under President Mikheil Saakashvili and Georgian Orthodox Church (GOC) officials made the reconstruction and reconsecration of the cathedral a priority. The reconstruction of Bagrati Cathedral, completed in September 2012, brought the differing aims of Georgian politicians, GOC officials, and architectural historians – the major players in the process – into sharp focus. This paper maintains that the rebuilding of Bagrati Cathedral was part of Saakashvili's political agenda, which merged with the interests of the GOC and worked against the objectives of architectural historians and the aims of academic principles of restoration and preservation. The result is that Bagrati has been rebuilt but is under threat of removal from the World Heritage List. The story of Bagrati's reconstruction has implications for the future of monument preservation and restoration in Georgia.